Influence of microstructure and surface treatment on the corrosion resistance of martensitic stainless steels 1.4116, 1.4034, and 1.4021. Issue 1 (10th December 2013) - Rosemann, P.; Müller, Th.; Babutzka, M.; Heyn, A.
<x xml:space="preserve">Abstract</x> In the last years, new approaches for the evaluation of the corrosion resistance of martensitic stainless steels were developed, which allow nearly non‐destructive as well as short‐term corrosion testing. This work analyzes the sensitive influence of microstructure and surface treatment on the corrosion resistance. The effect of alloy composition and microstructure, which is always present in addition to the influence of various surface treatments will be evaluated and discussed. The corrosion behavior was investigated with conventional evaluation of the pitting potential, electrochemical potentiodynamic reactivation (EPR), electrochemical noise (EN), and the "KorroPad" (KP) technique. EPR provided information about the passivation ability and the extent of chromium content reduction due to chromium carbide precipitation in the microstructure. The use of EN and KP aims to detect the influence of different surface treatment parameters on the corrosion resistance in a nearly non‐destructive way. Furthermore the results shall demonstrate the functionality and convenience of the short‐term corrosion test methods EN and KP in order to gain more acceptance within the scientific community. The results will allow the extraction of surface treatment effects on the corrosion behavior of the martensitic stainless steels 1.4116, 1.4034, and 1.4021.